2020
DOI: 10.1128/mbio.00602-20
|View full text |Cite
|
Sign up to set email alerts
|

Simian Immunodeficiency Virus-Infected Memory CD4+T Cells Infiltrate to the Site of Infected Macrophages in the Neuroparenchyma of a Chronic Macaque Model of Neurological Complications of AIDS

Abstract: Simian immunodeficiency virus (SIV)-infected nonhuman primates can serve as a relevant model for AIDS neuropathogenesis. Current SIV-induced encephalitis (SIVE)/neurological complications of AIDS (neuroAIDS) models are generally associated with rapid progression to neuroAIDS, which does not reflect the tempo of neuroAIDS progression in humans. Recently, we isolated a neuropathogenic clone, SIVsm804E-CL757 (CL757), obtained from an SIV-infected rhesus macaque (RM). CL757 causes a more protracted progression to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
(54 reference statements)
1
13
0
Order By: Relevance
“…Thus, to the best of our knowledge, this is the first report directly comparing two different HIV-1 Tat induction methods to evaluate changes in behavior and gene expression in a rodent model. We showed that Tat induction in iTat mice led to mild behavioral deficits when compared to WT controls including one or more of the following trends [1] higher anxiety levels depicted by reduced time spent in the open arms of EPM [2] altered ambulation during LMA [3] higher swim speeds in MWM [4] altered learning in T-maze. Simultaneously, we also depicted that gene expressions of [1] select inflammatory cytokines were unchanged, [2] MMPs were elevated, [3] TIMPs were altered depending on the duration of Tat exposure, subsequently impacting the brain MMP/TIMP balance.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Thus, to the best of our knowledge, this is the first report directly comparing two different HIV-1 Tat induction methods to evaluate changes in behavior and gene expression in a rodent model. We showed that Tat induction in iTat mice led to mild behavioral deficits when compared to WT controls including one or more of the following trends [1] higher anxiety levels depicted by reduced time spent in the open arms of EPM [2] altered ambulation during LMA [3] higher swim speeds in MWM [4] altered learning in T-maze. Simultaneously, we also depicted that gene expressions of [1] select inflammatory cytokines were unchanged, [2] MMPs were elevated, [3] TIMPs were altered depending on the duration of Tat exposure, subsequently impacting the brain MMP/TIMP balance.…”
Section: Discussionmentioning
confidence: 92%
“…During each trial, the mouse was allowed to swim until it climbed on the platform or for a maximum of 60 s, whichever was earlier. This pre-training was done so that the mice could learn the motor components of the task such as swimming and climbing onto a platform, and to reduce the bias of anxiety to a new environment during the subsequent phases [2] Acquisition phase: mice were then tested for their ability to locate a hidden platform using spatial cues around the room over four sessions (one session/day). Each session consisted of five trials, at 2-min intervals.…”
Section: Morris Water Maze (Mwm)mentioning
confidence: 99%
See 1 more Smart Citation
“…These researchers found HIV within the brains of these ToM mice, thus showing that T cells can traffic and establish viral reservoirs in the CNS in the absence of macrophages ( 46 ). A recent study using macaques infected with a neuropathogenic SIV clone, CL757, that results in progression to SIV-induced encephalitis (SIVE) in 50% of those infected, showed increased numbers of memory CD4 + T cells (mCD4s) and macrophages in the brains of macaques with SIVE ( 47 ). In addition, these researchers found replication-competent virus in macrophages of animals with SIVE and in mCD4s of animals with or without SIVE ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using macaques infected with a neuropathogenic SIV clone, CL757, that results in progression to SIV-induced encephalitis (SIVE) in 50% of those infected, showed increased numbers of memory CD4 + T cells (mCD4s) and macrophages in the brains of macaques with SIVE ( 47 ). In addition, these researchers found replication-competent virus in macrophages of animals with SIVE and in mCD4s of animals with or without SIVE ( 47 ). Given that only mCD4s harbored replication-competent virus in the absence of encephalitis, these authors suggest that mCD4s may be a potential viral reservoir within the brain ( 47 ).…”
Section: Discussionmentioning
confidence: 99%